Parafoveal Processing in Chinese Sentence Reading: Early Extraction of Radical Level Phonology - Luo, Jiefei; Wu, Yan; Jiao, Runkai (Frontiers in Psychology, 2018)
The present study separated radical level phonology from character level phonology to explore the reliance on phonology during Chinese sentence reading with eye movement recording in a boundary paradigm. Participants viewed sentences with either regular, irregular, orthographically dissimilar homophone, or orthographically dissimilar non-homophone previews for the targets. Both regular and irregular characters contained the target character as the phonetic radical, with the regular character sharing the identical sound with its target phonetic radical. In Experiment 1, the irregular previews were different from the target phonetic radicals both in the first consonant and final compound vowels. In Experiment 2, the irregular characters would be replaced by the semi-regular previews, which shared the same final compound vowels but not the first consonant with the target characters. The radical level phonological preview benefit was obtained by the comparison between regular and irregular characters, while the character level phonological preview benefit was shown by the visually dissimilar homophones compared with the unrelated control condition. The preview benefit from parafoveal regular characters compared with irregular characters was observed in the first fixation duration, suggesting the early activation of phonological codes at radical levels. However, this preview benefit depends on phonological overlapping between the phonetic radicals and their host characters; it could be activated only when the pronunciation of the phonogram was totally consistent with that of its phonetic radical. Furthermore, the null preview effect of visually dissimilar homophones indicates no activation of phonological codes at the character level during Chinese sentence reading.